Characterization of condensed tannins and carbohydrates in hot water bark extracts of European softwood species. (December 2015) - Bianchi, Sauro; Kroslakova, Ivana; Janzon, Ron; Mayer, Ingo; Saake, Bodo; Pichelin, Frédéric
Graphical abstract: The composition of hot water extracts from the bark of European softwood bark was investigated. The molecular structure of the extracted tannins and carbohydrates was analysed by liquid chromatography and mass spectrometry. Highlights: European softwood bark tannins structure significantly varies between species. The presence of phenolic glucosides is implied in most of the tannin structures analysed. A large amount of monomers and pectins are co-extracted with tannins. The most and least promising source for phenolics were larch and pine, respectively. Abstract: Condensed tannins extracted from European softwood bark are recognized as alternatives to synthetic phenolics. The extraction is generally performed in hot water, leading to simultaneous extraction of other bark constituents such as carbohydrates, phenolic monomers and salts. Characterization of the extract's composition and identification of the extracted tannins' molecular structure are needed to better identify potential applications. Bark from Silver fir ( Abies alba [Mill.]), European larch ( Larix decidua [Mill.]), Norway spruce ( Picea abies [Karst.]), Douglas fir ( Pseudotsuga menziesii [Mirb.]) and Scots pine ( Pinus sylvestris [L.]) were extracted in water at 60 °C. The amounts of phenolic monomers, condensed tannins, carbohydrates, and inorganic compounds in the extract were determined. The molecular structures of condensed tannins and carbohydrates were also investigated (HPLC-UV combined with thiolysis, MALDI-TOF mass spectrometry, anion exchange chromatography). Distinct extract compositions and tannin structures were found in each of the analysed species. Procyanidins were the most ubiquitous tannins. The presence of phenolic glucosides in the tannin oligomers was suggested. Polysaccharides such as arabinans, arabinogalactans and glucans represented an important fraction of all extracts. Compared to traditionally used species (Mimosa and Quebracho) higher viscosities as well as faster chemical reactivities are expected in the analysed species. The most promising species for a bark tannin extraction was found to be larch, while the least encouraging results were detected in pine. A better knowledge of the interaction between the various extracted compounds is deemed an important matter for investigation in the context of industrial applications of such extracts.